Luto na maternidade: construção de cartilha para cuidados em situação de óbito perinatal - Duarte, Mariane Graciano [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Health professionals use some tactics to protect themselves psychically from the suffering experienced by their patients. One of the ways of protection is the conception that the maternity sector is a place where new lives emerge and not where they end. However, motherhood can be marked by negative events, accompanied by losses rather than gains, making death a controversial and challenging issue in this environment. Therefore, the objective of this research was to develop an instructional material, in booklet format, that assists health professionals in approaching and caring for mothers, fathers and family members after gestational or neonatal loss in maternity. This is a methodological study, for the construction of an educational technology, which adopted the steps of: submission of the project to the ethics committee, survey of experiences and demands of the target population through a qualitative study, bibliographic survey and elaboration of educational material. The material was built through the stages of systematization of the content; selection and elaboration of illustrations; composition of the booklet and editorial criteria used. The results were presented in the production of instructional material in booklet format, entitled: "Dealing with bereavement in maternity - guidelines for nursing professionals". In systematizing the content of the material, the following contents were listed, considered most relevant to guide the care provided by health professionals to be addressed: 1) maternity; 2) what is mourning; 3) the health professional facing death and mourning; 4) how to deal with maternity loss; 5) contact with the baby; 6) lines that should be avoided; and 7) legal and bureaucratic information. The material is expected to help professionals in the conduct of nursing care, favoring the grieving process of women, as well as their partner and family, in view of the painful situation of perinatal loss.

Os profissionais de saúde utilizam algumas táticas com intuito de se resguardar psiquicamente do sofrimento vivenciado por seus pacientes. Entre uma das maneiras de proteção está a concepção de que setor da maternidade seja um lugar onde surgem novas vidas e não onde elas acabam. Entretanto a maternidade pode ser marcada por acontecimentos negativos, acompanhados por perdas ao invés de ganhos, tornando a morte um assunto polêmico e desafiador nesse meio. Diante disso, o objetivo desta pesquisa foi elaborar um material instrutivo, em formato de cartilha, que auxilie profissionais de saúde na abordagem e no cuidado de mães, pais e familiares após perda gestacional ou neonatal na maternidade. Trata-se de um estudo do tipo metodológico, para construção de uma tecnologia educativa, o qual adotou as etapas de: submissão do projeto ao comitê de ética, levantamento de vivências e demandas da população alvo por meio de um estudo qualitativo, levantamento bibliográfico e elaboração do material educativo. O material foi construído através das etapas de sistematização do conteúdo; seleção e elaboração das ilustrações; composição da cartilha e critérios editoriais utilizados. Os resultados apresentaram-se na produção de material instrutivo em formato de cartilha, com o título: "Lidando com o luto na maternidade – orientações aos profissionais de enfermagem". Na sistematização do conteúdo do material, foram elencados os seguintes conteúdos, considerados mais relevantes para nortear o cuidado prestado pelos profissionais de saúde para serem abordados: 1) a maternidade; 2) o que é luto; 3) o profissional de saúde frente a morte e o luto; 4) como lidar com a perda na maternidade; 5) o contato com o bebê; 6) falas que devem ser evitadas; e 7) informações legais e burocráticas. Espera-se que o material auxilie os profissionais na condução dos cuidados de enfermagem, favorecendo o processo de luto da mulher, assim como seu parceiro e familiares, frente à dolorosa situação que é a perda perinatal.
Bereavement in maternity: construction of a booklet for perinatal death care
Keywords: Bereavement; Maternity; Health personnel; Luto; Maternidade; Profissionais de saúde